Pengukuran Keberhasilan Penggunaan Internet Banking di Bank Rakyat Indonesia Kota Denpasar - Dewi, A.A. Putri Pintari; Wirakusuma, Made Gede; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
This study assesses the success of using internet banking using the DeLone & McLean (D&M) model with the aim of measuring the success of using internet banking technology. The research was conducted at Bank Rakyat Indonesia (BRI) Denpasar City with 150 internet banking users as respondents who were selected through accidental sampling technique. The test results show that the quality of information, the quality of information systems, the quality of service has a positive effect on the interest in using internet banking and the interest in using it has a positive effect on the net benefit. The implications of this study include two things, namely theoretical implications and practical implications, on the theoretical implications of information quality, information system quality, service quality and user interest have an effect on the net benefit or net benefits of using internet banking. The practical implication is that the high interest in using internet banking can create net benefits for customers of PT Bank Rakyat Indonesia Denpasar City. Keywords: D&M models; Successful Use of the System; Internet Banking .